The influence of 120 minutes of competitive match-play on recovery and subsequent match performance: a case study in professional soccer players - Harper, L. D.; Winder, N.; Kilduff, L. P.; West, D. J.; Stevenson, E.; Russell, M. (International Science and Football Association Conference 2016, 2016)
Introduction: The influence of 120 min of soccer match-play (i.e., matches requiring a 30 min extra-time period; ET), on physical and technical performance, and functional and biochemical measures of recovery has recently been investigated (Harper et al., 2014; Russell et al., 2015). However, the effect of 120 min of match-play on performance and subjective measures of post-match recovery requires investigation; especially in the context of subsequent match-play. The use of Global Positioning Systems (GPS) was permitted during competitive professional soccer matches by FIFA in July 2015, allowing soccer clubs to use this technology to derive information on player performance during competitive matches. Purposes: 1) use GPS-derived data to assess the impact of playing a competitive match requiring ET on a competitive 90 min match played 64 h later; 2) elucidate the influence of ET on post-match recovery.